Does innovation promote economic growth? Evidence from European countries - Rana P. Maradana; Rudra P. Pradhan; Saurav Dash; Kunal Gaurav; Manju Jayakumar; Debaleena Chatterjee (Journal of Innovation and Entrepreneurship, 2017)
The paper examines the long-run relationship between innovation and per capita economic growth in the 19 European countries over the period 1989-2014. This study uses six different indicators of innovation: patents-residents, patents-non-residents, research and development expenditure, researchers in research and development activities, high-technology exports, and scientific and technical journal articles to examine this long-run relationship with per capita economic growth. Using cointegration technique, the study finds evidence of long-run relationship between innovation and per capita economic growth in most of the cases, typically with reference to the use of a particular innovation indicator. Using Granger causality test, the study finds the presence of both unidirectional and bidirectional causality between innovation and per capita economic growth. These results vary from country to country, depending upon the types of innovation indicators that we use in the empirical investigation process. Most importantly, the study finds that all these innovation indicators are considerably linked with per capita economic growth. This particular linkage is either supply-leading or demand-following in some occasions, while it is the occurrence of both in some other occasions. The policy implication of this study is that countries should recognize the differences in innovation and per capita economic growth in order to maintain sustainable development in these countries.
Keywords: O43; O16; E44; 650; Innovation; Per capita economic growth; Cointegration; Granger causality; European countries